Elevated Cerebrospinal Fluid Neopterin Concentration Is Associated with Disease Severity in Acute Puumala Hantavirus Infection. (30th July 2013) - Hautala, Timo; Partanen, Terhi; Sironen, Tarja; Rajaniemi, Saara-Mari; Hautala, Nina; Vainio, Olli; Vapalahti, Olli; Kauma, Heikki; Vaheri, Antti
Abstract : Nephropathia epidemica (NE) caused by Puumala hantavirus (PUUV) is the most common hemorrhagic fever with renal syndrome (HFRS) in Europe. The infection activates immunological mechanisms that contribute to the pathogenesis and characteristics of the illness. In this study we measured cerebrospinal fluid (CSF) neopterin concentration from 23 acute-phase NE patients. We collected data on kidney function, markers of tissue permeability, haemodynamic properties, blood cell count, length of hospitalisation, inflammatory parameters, and ophthalmological properties. The neopterin levels were elevated (>5.8 nmol/L) in 22 (96%) NE-patients (mean 45.8 nmol/L); these were especially high in patients with intrathecal PUUV-IgM production (mean 58.2 nmol/L, P = 0.01 ) and those with elevated CSF protein concentrations (mean 63.6 nmol/L, P < 0.05 ). We also observed a correlation between the neopterin and high plasma creatinine value (r = 0.66, P = 0.001 ), low blood thrombocyte count (r = - 0.42, P < 0.05 ), and markedly disturbed refractory properties of an eye (r = 0.47, P < 0.05 ). Length of hospitalisation correlated with the neopterin (r = 0.42, P < 0.05 ; male patients r = 0.69, P < 0.01 ). Patients with signs of tissue oedema and increased permeability also had high neopterin concentrations. These results reinforce the view that PUUV-HFRS is a general infection that affects the central nervous system and the blood-brain barrier.